Mutagenic DNA Polymerase in Human Leukemic Cells - Springgate, Clark F. (1973)
Evidence is presented that DNA polymerases from human leukemic cells are mutagenic. Nucleic acid-free extracts of acute lymphoblastic leukemic cells polymerized about 10-times more dCTP using poly(dA-dT)·poly(dA-dT) as a template than did extracts from normal lymphocytes. Mutagenic DNA polymerases could perhaps play an important role in tumor progression.